Sigmoid Resection and Primary Anastomosis Without Any Diversion or Exteriorization for Impacted Foreign Body in Sigmoid Colon - Moniruddin, ABM; Faisal, M Fardil Hossain; Chowdhury, Salma; Hasan, Tanvirul; Rafique, Romana; Banerjee, Gourav; Khan, Md Rashed; Rahman, Md Masudar; Sharif, Sayeed Bin (KYAMC Journal, 2020)
Colorectal Resections are very often required as an essential surgical procedure for various diseases. These resections are usually accompanied with various forms of diversions with or without primary colo-colonic or colorectal anastomosis. Classically, these are usually preceded by a standard form of bowel preparation. Here, a different form of colorectal surgery without preceding bowel preparation, colorectal resection and primary anastomosis were done, without any covering or defunctioning ileostomy or any other form of diversion or exteriorization and envisaged no complication. A psychiatric adult patient presented with self-introduction of a large foreign body (bobbin) through his anus. On laparotomy, FB (bobbin) impacted at the apex of the loop of sigmoid colon. It was so intensely impacted that milking towards the rectum without serious injury was totally impossible. Sigmoid resection and primary colorectal anastomosis without any form of ileostomy or similar type of diversion or exteriorization was performed. Just before anastomosis, faecal matters were removed as far as possible all from remaining both proximal and distal segments. Then digital anal stretching was done and put a transanastomotic flatus tube through anus. The flatus tube was removed on the 7th post operative day. The outcome was smooth and uneventful. KYAMC Journal Vol. 10, No.-4, January 2020, Page 214-218